Image-Building of Chinese Motorcycle Enthusiasts on Chinese Social Media Douyin - Zhang Ziliang (SHS Web of Conferences)
In the post-COVID era, the rise of domestic motorcycle culture and platforms like Douyin have given motorcycles stronger social communication attributes, reducing their function as mere tools. More ordinary people have access to motorcycles, and motorcycle-related topics on the Douyin platform will be more discussed and controversial. This paper will analyze the current public opinion environment related to motorcycle topics on the Douyin platform, and discuss the role played by the social media platform Douyin in spreading motorcycle riding culture and shaping the image of motorcycle enthusiasts. This research will adopt the method of quantitative analysis questionnaire to study the usage habits of motorcycle enthusiasts and the motivation for sharing motorcycle-related content on Douyin and analyze the current status and problems of Douyin’s news reports on motorcycles. Douyin has played an active role in promoting motorcycle culture and shaping the image of motorcycle enthusiasts, while constantly influencing and promoting the revision and improvement of relevant laws and regulations towards motorcycle riding. However, due to more negative news reports, society’s aversion to motorcycle riding culture and motorcycle enthusiasts will lead to an antagonistic relationship between car drivers and motorcycle riders, which is not conducive to the positive image-building of motorcycle enthusiasts.